Resilience and sustainability of the water sector during the COVID-19 pandemic - Goldin, J.; Nhamo, L.; Ncube, B.; Zvimba, J. N.; Petja, B.; Mpandeli, S.; Nomquphu, W.; Hlophe-Ginindza, S.; Greeff-Laubscher, M. R.; Molose, V.; Lottering, S.; Liphadzi, S.; et al. (MDPI, 2022)
The COVID-19 pandemic brought unprecedented socio-economic changes, ushering in a “new (ab)normal” way of living and human interaction. The water sector was not spared from the effects of the pandemic, a period in which the sector had to adapt rapidly and continue providing innovative water and sanitation solutions. This study unpacks and interrogates approaches, products, and services adopted by the water sector in response to the unprecedented lockdowns, heralding novel terrains, and fundamental paradigm shifts, both at the community and the workplace. The study highlights the wider societal perspective regarding the water and sanitation challenges that grappled society before, during, after, and beyond the pandemic. The premise is to provide plausible transitional pathways towards a new (ab)normal in adopting new models, as evidenced by the dismantling of the normal way of conducting business at the workplace and human interaction in an era inundated with social media, virtual communication, and disruptive technologies, which have transitioned absolutely everything into a virtual way of life. As such, the novel approaches have fast-tracked a transition into the 4th Industrial Revolution (4IR), with significant trade-offs to traditional business models and human interactions.